Does infant feeding method influence the incidence and pattern of morbidities among human immunodeficiency virus-exposed uninfected nigerian infants? - Olusoga Babatunde Ogunfowora; Tinuade Adetutu Ogunlesi; Abiodun Folashade Adekanmbi; Victor Ayodeji Ayeni (Wolters Kluwer Medknow Publications, 2017)
Background: Human immunodeficiency virus (HIV)-exposed infants enrolled into the prevention of mother-to-child transmission of HIV program generally receive antiretroviral therapy (ARV), but the feeding methods differ based on several socioeconomic and cultural differences. Objective: The objective of the study was to examine the incidence and pattern of morbidities among HIV-exposed uninfected (HEU) Nigerian infants and determine any relationship with infant feeding methods. Methods: A review of the hospital records of all HEU infants attending the Virology Clinic of Olabisi Onabanjo University Teaching Hospital, Sagamu, Nigeria, between July 2013 and June 2015, was done. The recorded data included biodemographic profile, social parameters, feeding methods, anthropometry, and morbidities. The feeding method groups were statistically compared in relation to the various morbidities. Results: Out of 119 children, 81.5% were exclusively breastfed, whereas 18.5% had exclusive breast milk substitute feeding. About half had various morbidities which included upper airway infections (UAIs) (16.8%), malaria (15.9%), malnutrition (8.4%), diarrhea (8.4%), and pneumonia (2.5%). The frequencies of these conditions were similar among infant groups irrespective of feeding method. The infants with and without morbidities were comparable in terms of the frequency of exclusive breastfeeding (80.3% vs. 82.8%). Low family socioeconomic status (SES) (odds ratio [OR] = 7.7) and ARV use (OR = 0.4) among infants were predictors of morbidities among HEU infants. Conclusion: The incidence and pattern of morbidities among HEU infants showed no relation to the mode of feeding. Rather, family SES and the use of antiretroviral drugs were predictors of morbidities among HEU infants.